A Ru–Ru pair housed in ruthenium phthalocyanine: the role of a "cage" architecture in the molecule coupling with the Ag(111) surface. Issue 2 (16th December 2016) - Alippi, Paola; Lanzilotto, Valeria; Paoletti, Anna Maria; Mattioli, Giuseppe; Zanotti, Gloria; Pennesi, Giovanna; Filippone, Francesco; Cossaro, Albano; Verdini, Alberto; Morgante, Alberto; Amore Bonapasta, Aldo
Abstract : A combined experimental and theoretical study on the Ru–Pc dimer on Ag(111) proves surface-to-molecule charge transfer and predicts magnetic moment quenching. Abstract : A number of studies have investigated the properties of monomeric and double-decker phthalocyanines (Pcs) adsorbed on metal surfaces, in view of applications in spintronics devices. In a combined experimental and theoretical study, we consider here a different member of the Pcs family, the (RuPc)2 dimer, whose structure is characterized by two paired up magnetic centers embedded in a double-decker architecture. For (RuPc)2 on Ag(111), we show that this architecture works as a preserving cage by shielding the Ru–Ru pair from a direct interaction with the surface atoms. In fact, while noticeable surface-to-molecule charge transfer occurs with the ensuing quenching of the molecular magnetic moment, such phenomena occur here in the absence of a direct Ru–Ag coupling or structural rearrangement, at variance with other Pcs and thanks to the above shielding effect. These unique properties of the (RuPc)2 architecture are expected to permit an easy control of the surface-to-molecule charge-transfer process as well as of the molecular magnetic properties, thus making the (RuPc)2 dimer a significant paradigm for innovative "cage" structures as well as a promising candidate for applications in spintronics nano or single-molecule devices.